Correlation of Coagulopathy of Trauma and Revised Trauma Score in Predicting Outcome in Trauma Patients - Thakur, DK; Sharma, MR; Lohani, I (Journal of Institute of Medicine Nepal, 2016)
Background: Trauma is a major worldwide public health problem. It is one of the leading causes of death and disability in both industrialized and developing countries. Coagulopathy is present immediately at admission in 25% of trauma patients and is associated with a 5-fold increase in mortality. The Revised Trauma Score (RTS) is a physiological scoring system, with high inter-rater reliability and demonstrated accuracy in predicting death. The purpose of this study was to correlate coagulopathy of trauma and RTS in predicting outcome in trauma patients.Methods: In this prospective study, 75 traumatic patients were studied over a period of one year (May 2010 to April 2011) in The Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Patients were evaluated on arrival in emergency room (ER) and data was collected on patients' demography, time from injury to arrival in ER, fluid administered before referral, vital signs, GCS and RTS was calculated.Coagulation profile was determined by measuring prothombin time(PT) and activated partial thromboplastin time(aPTT).Results: Of 75 patients studied, 84% (63) were male and 16% (12) were female with 47%(35) in the 21-40 year age group. Road traffic accident was most common type of injury (60%) followed by fall from height (29%). The median time after injury was 8 hours and fluid administration before referral was 1000ml. Traumatic coagulopathy was present in 24%(18) of patients and mortality was 16% (12). Coagulopathy was significantly associated with time of presentation in ER following injury (P=0.01),GCS(P=0.012), SBP(P